APPLICATION POLARIMETRY FOR MEASUREMENT OF RELIEF - Tronko, Vladimir; Romanenko, Victor; Klochan, Arsen (Proceedings of National Aviation University (archive), 2015)
The article discusses modern geodetic measurement methods of relief, their advantages and disadvantages. It is also offered a polarimetric measurement method of relief. This method is intended for measuring relief and can also be used to measure slope road and airport paving, railways to geometric description of the surface complex engineering objects, such as bridges, roofs of buildings, architectural elements.